Effect of vedolizumab (anti-α4β7-integrin) therapy on histological healing and mucosal gene expression in patients with UC. Issue 1 (7th October 2016) - Arijs, Ingrid; De Hertogh, Gert; Lemmens, Bart; Van Lommel, Leentje; de Bruyn, Magali; Vanhove, Wiebe; Cleynen, Isabelle; Machiels, Kathleen; Ferrante, Marc; Schuit, Frans; Van Assche, Gert; Rutgeerts, Paul; et al.
Abstract : Objective: Lymphocyte recruitment to the inflamed gut is increased in UC. Inhibition of this cell trafficking by vedolizumab (VDZ) was successful in inducing and maintaining remission and in induction of endoscopic mucosal healing. There are no data on histological healing with VDZ. We studied histological changes following VDZ therapy and compared gene expression in patients with UC before and after therapy. Design: Forty-one patients with UC from GEMINI I and LTS were studied before and at three time points (weeks 6/12/52) following VDZ therapy. Colonic biopsies were scored using the Geboes index and correlated with Mayo endoscopic subscore. Gene expression was analysed using Affymetrix gene arrays. Results: Fifty-five per cent of patients achieving endoscopic healing (= Mayo endoscopic subscore 0–1) with VDZ at the studied time points also had histological healing (= Geboes grade 0–1). In most healers, some residual histological changes (eg, disturbed architecture and increased mononuclear cell infiltrate) were still observed, although this was less at week 52. VDZ restored expression of many inflammatory genes in patients with endoscopic healing only at week 52 and not before. In VDZ healers, the expression of many genes remained dysregulated at weeks 6/12/52 compared with controls. Conclusions: VDZ induces histological healing in >50% of patients with endoscopic healing, with maximal effect at week 52. VDZ also restored, although incompletely, the colonic expression of many immune-related genes in patients with UC achieving endoscopic healing at week 52. However, persistent histological and gene dysregulations did remain even in healers, suggesting that maintenance therapy will be necessary to control the intestinal inflammation. Trial registration numbers: NCT00783718 and NCT00790933 ; post-results.